Association of two new Coryphasia species (Araneae, Salticidae) with tank-bromeliads in southeastern Brazil: Habitats and patterns of host plant use - Romero, Gustavo Q. [UNESP]; Santos, Adalberto J.; Wienskoski, Eduardo H.; Vasconcellos Neto, João (Amer Arachnological Soc, 2007)
Two allopatric species of Coryphasia (Araneae: Salticidae), both described for the first time in this study, have been found associated with Bromeliaceae in distinct phytophysiognomies (e.g., inselbergs, highland forests and restingas) from southeastern Brazil. In this study, we investigated whether these salticids were associated specifically with bromeliads, and whether they used bromeliads of different species and sizes in distinct geographic regions. The Coryphasia species were rarely found outside bromeliads, occupied larger bromeliad species among those available, and were generally more frequent on bromeliads in open areas, such as inselbergs on mountain tops. The two Coophasia species were observed submerging in phytotelmata, possibly as an anti-predatory behavior. The patterns of spatial and microspatial distribution and the submergence behavior of these species were similar to those of other bromeliad-dwelling salticids, which suggests a convergence among spiders that live on bromeliads.
Keywords: animal-plant interactions; Bromeliaceae; spider; Specific association; submergence behavior; phytotelmata